2003
DOI: 10.1002/eji.200324294
|View full text |Cite
|
Sign up to set email alerts
|

T cell development and function in CrkL‐deficient mice

Abstract: The adapter protein CrkL has been implicated in multiple signal transduction pathways in hematopoietic cells. In T lymphocytes, the recruitment of CrkL-C3G complexes has been correlated with hyporesponsiveness, implicating CrkL as a potential negative regulator. To test this hypothesis we examined T cell activation in CrkL-deficient mice. The CrkL -/-genotype was partially embryonic lethal. In viable CrkL -/-mice, peripheral blood counts were normal. The thymus from CrkL -/-mice had 40% fewer cells compared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 52 publications
1
14
0
Order By: Relevance
“…We conclude that reduction in B cell outgrowth from Crkl − / − and Crkl +/ − fetal liver in Whitlock-Witte cultures was not due to a deficiency in B cell progenitors. This finding is consistent with previous findings that there was no difference in the ability of hematopoietic progenitor cells derived from Crkl − / − fetal livers to reconstitute the bone marrow of irradiated Rag2 −/ − recipients compared to Wt with similar numbers of circulating B220+ cells (32). …”
Section: Resultssupporting
confidence: 93%
“…We conclude that reduction in B cell outgrowth from Crkl − / − and Crkl +/ − fetal liver in Whitlock-Witte cultures was not due to a deficiency in B cell progenitors. This finding is consistent with previous findings that there was no difference in the ability of hematopoietic progenitor cells derived from Crkl − / − fetal livers to reconstitute the bone marrow of irradiated Rag2 −/ − recipients compared to Wt with similar numbers of circulating B220+ cells (32). …”
Section: Resultssupporting
confidence: 93%
“…Inhibition of T-lymphoblast proliferation is associated with downregulation of LMNB1 protein (78). CRKL is targeted by 4 miRNAs and involved in signal transduction through WIP, JNK and Zap70(79). IQGAP1, targeted by 2 miRNAs, regulates lymphocyte cytoskeleton rearrangement in the immune synapse (80).…”
Section: Resultsmentioning
confidence: 99%
“…Another CRKL knockout study had shown shortly before this, that the loss of CRKL can lead to multiple and severe developmental defects 'in utero', particularly in neural crest-derived cells [100]. Further defects were later seen when fibroblasts derived from these mice were analysed in more detail [101], but T-cell function does not appear to be affected [102]. Taken together, these findings suggest that Crk and CRKL proteins, although widely expressed and of considerable homology, are not merely redundant adaptors.…”
Section: Crk Family Adaptorsmentioning
confidence: 93%